Impact of military footwear type and a load carriage workload on slip initiation biomechanics. (28th August 2020) - Chander, Harish; Arachchige, Sachini N.K. Kodithuwakku; Wilson, Samuel J.; Knight, Adam C.; V, Reuben F. Burch; Carruth, Daniel W.; Wade, Chip; Garner, John C.
The impact of military footwear and workload on slip incidence and severity have been previously reported. Further analysis of slip initiation biomechanics is warranted in attempt to prevent slips. Sixteen participants were tested with two military boots, standard (STD) and minimalist (MIN), before (PRE) and after (POST) a load carrying task during normal gait (NG), unexpected (US) and expected (ES) slips. Joint kinematics, ground reaction forces and muscle activity from the slipping leg were analysed using a 2 (MIN-STD) × 2 (PRE-POST) × 3 (NG-US-ES) repeated measures ANOVA. Results revealed significant gait modifications due to footwear and gait. STD exhibited greater ankle dorsiflexion and knee flexion, lowered ground reaction forces and increased muscle activity compared to MIN. US and ES elicited greater plantar flexion and knee flexion angles while requiring a greater muscle activation compared to NG. Findings can aid in understanding slip initiation biomechanics, for footwear design and promoting safety.